Comparative Genomics of Two Independently Enriched “Candidatus Kuenenia Stuttgartiensis” Anammox Bacteria - Speth, Daan R.; Hu, Baolan; Bosch, Niek; Keltjens, Jan; Stunnenberg, Hendrik; Jetten, Mike (Frontiers in Microbiology, 2012)
Bacteria capable of anaerobic oxidation of ammonium (anammox) form a deep branching clade within the Planctomycetes. Although the core metabolic pathway of anammox bacteria is largely resolved, many questions still remain. Data mining of the (meta) genomes of anammox bacteria is a powerful method to address these questions or identify targets for further study. The availability of high quality reference data greatly aids such analysis. Currently, only a single “near complete” (∼98%) reference genome of an anammox bacterium is available; that of model organism “Candidatus Kuenenia stuttgartiensis.” Here we present a comparative genomic analysis of two “Ca. K. stuttgartiensis” anammox bacteria that were independently enriched. The two anammox bacteria used are “Ca. K. stuttgartiensis” RU1, which was originally sequenced for the reference genome in 2002 and “Ca. K. stuttgartiensis” CH1, independently enriched from a Chinese wastewater treatment plant. The two different “Ca. Kuenenia” bacteria have a very high sequence identity (>99% at nucleotide level) over the entire genome, but 31 genomic regions (average size 11 kb) were absent from strain CH1 and 220 kb of sequence was unique to the CH1 assembly. The high sequence homology between these two bacteria indicates that mobile genetic elements are the main source of variation between these geographically widely separated strains. Comparative analysis of the RU1 and CH1 assemblies led to the identification of 49 genes absent from the reference genome. These include a leucyl-tRNA-synthase, the absence of which led to the estimation of the 98% completeness of the reference genome. Finally, a set of 244 genes was present in the reference genome, but absent in the RU1 and CH1 assemblies. These could represent either identical gene duplicates or assembly errors in the published genome. We are confident that this analysis has further improved the most complete available high quality reference genome of an anammox bacterium and will aid further studies on this globally important group of organisms.